2011
DOI: 10.1111/j.1365-2443.2011.01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid taste receptor regulates insulin secretion in pancreatic β-cell line MIN6 cells

Abstract: Amino acids such as L-glutamate and L-arginine are potent stimuli for insulin secretion from pancreatic b-cells. However, the precise molecular mechanisms of amino acid-induced insulin secretion have only partly understood. In this study, we show here that mouse pancreatic b-cell line MIN6 cells expressed amino acid taste receptor (heterodimer of type 1 taste G protein-coupled receptor member 1 and member 3; Tas1R1 and Tas1R3, respectively). We found that administration of L-glutamate or L-arginine to MIN6 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 50 publications
(76 reference statements)
1
33
0
1
Order By: Relevance
“…Total Internal Reflection Fluorescence (TIRF) Imaging of tPA-GFP Release-To monitor the release of tPA-GFP at the single vesicle level, we used a TIRF microscope similar to that described previously (14,19,20). Imaging was performed in modified RB (130 mM NaCl, 3.6 mM KCl, 0.5 mM NaH 2 PO 4 , 0.5 mM MgSO 4 , 1.5 mM CaCl 2 , 10 mM HEPES, 2 mM NaHCO 3 , 5 mM glucose, pH 7.4).…”
Section: Chemicals and Expression Vectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total Internal Reflection Fluorescence (TIRF) Imaging of tPA-GFP Release-To monitor the release of tPA-GFP at the single vesicle level, we used a TIRF microscope similar to that described previously (14,19,20). Imaging was performed in modified RB (130 mM NaCl, 3.6 mM KCl, 0.5 mM NaH 2 PO 4 , 0.5 mM MgSO 4 , 1.5 mM CaCl 2 , 10 mM HEPES, 2 mM NaHCO 3 , 5 mM glucose, pH 7.4).…”
Section: Chemicals and Expression Vectorsmentioning
confidence: 99%
“…To analyze the TIRF imaging data, single exocytotic events were selected manually, and the average fluorescence intensity of an individual vesicle in a 0.7 m ϫ 0.7 m square placed over the vesicle center was calculated (14,19,20). To distinguish between fusion events and retreated vesicles, we focused on fluorescence changes just before the disappearance of fluorescent signals.…”
Section: Chemicals and Expression Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports negate the function of lactisole as an inhibitor of the glucose-sensing receptor in rodents. In this regard, Oya et al (2011) reported recently that lactisole inhibits the umami receptor function in MIN6 cells. Their results suggest that mouse T1R3 (mT1R3) is not totally insensitive to lactisole.…”
Section: Introductionmentioning
confidence: 99%
“…To observe the release of BDNF-Venus at the single-vesicle level, we used a total internal reflection fluorescence (TIRF) microscope similar to those described previously (Mori et al 2011, Oya et al 2011, 2013a,b, Sato et al 2012, Kitaguchi et al 2013. Briefly, a high numerical aperture objective lens (CFI Apochromat TIRF, 100!, NAZ1.49, Nikon, Tokyo, Japan) was mounted on an inverted microscope (Ti-E-Perfect focus system, Nikon), and incident light for total internal reflection illumination was introduced from the high numerical aperture objective lens through a single-mode optical fiber and two illumination lenses (TI-TIRF, Nikon).…”
Section: Total Internal Reflection Fluorescence Imagingmentioning
confidence: 99%